Vivências diante do desligamento institucional compulsório: a perspectiva de adolescentes na iminência da maioridade - Araujo, Ivy Campista Campanha de (2023)
According to the regulatory frameworks in the scope of the Child and Adolescent Rights Guarantee System, the host institution for children and adolescents is configured as a moment of transitory support. However, some adolescents do not return home, nor are they adopted, often resulting in institutionalization until age of majority. This is the scenario in which the experience compulsory institutional disconnected by age of majority occurs. Based on the adolescents' reports, the aim of this study was to understand the experiences of adolescents on the verge of compulsory institutional disconnected, using Winnicott's Theory of Human Maturity (TAHW) as a guideline for understanding the phenomenon in question. This is a qualitative research based on a multiple case study. The method consisted in the application of the instruments: semi-structured Interviews, Field Diary and the Life Line technique, which were carried out with to six adolescents in host institution, totaling twenty-five interviews, carried out through sixteen insertions in the field. The analysis of the results showed that the participants mobilized more to talk about the losses and gains of living in an institution, than the institutional disconnection, demonstrating emotional health in wanting to live the immaturity inherent in being an adolescent towards integration. The participants heard at all stages of the research, despite the ambiguities present in their reports, considered the institution as a space in which they found a good enough environment. It was also observed that the adolescents did not feel supported by any other public policy, in addition to those they had access to through the institution. It is concluded that the research made it possible to expand information about adolescents in institutional care and the expectations and anxieties related to the process of compulsorily leaving the institution. It was also highlighted that support and support policies for adolescents and the Institutional Reception Service could help to experience the challenges presented by adolescents.